Comparison of the therapeutic efficacy and safety of combined oral tranexamic acid and topical hydroquinone 4% treatment vs. topical hydroquinone 4% alone in melasma: a parallel‐group, assessor‐ and analyst‐blinded, randomized controlled trial with a short‐term follow‐up. (20th October 2016) - Lajevardi, Vahideh; Ghayoumi, Afsaneh; Abedini, Robabeh; Hosseini, Hamed; Goodarzi, Azadeh; Akbari, Zahra; Hedayat, Kosar
Summary: Background: Melasma's high prevalence and profound psychological impact on patients necessitate efficacious, economical, and safe therapeutic interventions. Adjunctive therapies such as tranexamic acid (TA) can enhance the therapeutic effect of standard treatments like hydroquinone 4% cream (HQ). Objective: To conduct an assessor‐ and analyst‐blinded, parallel, superiority, randomized controlled trial to compare the clinical efficacy and safety of oral TA plus HQ vs . HQ alone in melasma treatment. Materials and Methods: A total of 100 eligible patients with symmetric facial melasma were assigned to the intervention (250 mg thrice daily oral TA plus HQ 4% cream nightly) or the control group (HQ 4% cream only). Following 3 months of treatment, MASI (melasma area and severity index) score reduction was calculated as the primary outcome measure. After a 3‐month follow‐up, relapse was also assessed. Results: A total of 88 patients completed the study. At the end of the 6‐month period, the overall mean of the MASI score in the intervention group was 1.8 points lower than in the controls (95% confidence interval, 0.36–3.24, P = 0.015) but the relapse rate was not significantly different (30% vs . 26% in the treatment vs . control group, respectively). Side effect occurrence was also similar, but treatment satisfaction was higher in the intervention group than the controls, with 82.2% vs . 34.95 of patients reporting moderate‐to‐complete satisfaction, respectively ( P < 0.001). Conclusions: Oral TA can enhance the efficacy of hydroquinone 4% cream in melasma treatment, but the high incidence of relapse suggests that treatment effects may be temporary, warranting more investigation.